Tuberculosis screening, testing, and treatment of U.S. health care personnel: Recommendations from the National Tuberculosis Controllers Association and CDC, 2019. Issue 8 (25th July 2019) - Sosa, Lynn E.; Njie, Gibril J.; Lobato, Mark N.; Morris, Sapna Bamrah; Buchta, William; Casey, Megan L.; Goswami, Neela D.; Gruden, MaryAnn; Hurst, Bobbi Jo; Khan, Amera R.; Kuhar, David T.; Lewinsohn, David M.; et al.
Abstract : This article presents updated recommendations for screening health care workers for tuberculosis, including eliminating serial screening in the absence of exposure or ongoing transmission.